Uji Aktivitas Minyak Atsiri Bunga Kamboja (Plumeira acuminate Ait) sebagai Repellent terhadap Nyamuk Aedes aegypti - Tika Novita Sari; Lucia Vita Inandha Dewi; Dyah Susilowati (Jurnal Farmasi Indonesia, 2014)
Repellent is a material that has the ability to protect humans from mosquito bites. Repellent have contains active ingredients that can interrupt mosquitoes ability to find their host. Essensial oil of frangipani flower contains has active materials, such as geraniol, linalool and sitronelol. This study aimed to determine the ability of frangipani oil as repellent to prevent bites of Aedes aegypti. This repellent activity was conducted with inserting the hand alternately between treatment and control into test cage repellent each containing 50 mosquitoes. It was about 3 hours treatment with observation for 5 minutes at each intervals of 1 hour. The oil concentration used were 1%, 3%, 6%, 12,5% and 25% with DEET 13 % as a positive control and distilled water as negative control. The Observation data was any concentration of power protection essential oil. Analysis of the data has been using by one – way ANOVA test (p= 0,000), followed by a different average Tukey HSD with α = 0,05 (p= 0,000). Effective dose value (ED50) for protection against Aedes aegypti by 50% was calculated by probit analysis. The result of this study was the frangipani oil has a potential effect as repellent to Aedes aegypti with ED50 of 1,3357%. The higher concentration will increase the potential repellent, where as the longer it will reduce the potential repellent treatment.